1975
DOI: 10.1113/jphysiol.1975.sp011157
|View full text |Cite
|
Sign up to set email alerts
|

An alkyl etherase in rat liver.

Abstract: SUMMARY1. Diethyl ether, which is known to be partly metabolized in vivo, has been found to show an 02 uptake with the rat liver microsomal membranes; a similar reaction is given with other short chain aliphatic ethers, isopropyl and n-butyl ether.2. The 'etherase' reaction is optimal at pH 7-2-7-4 and is not accompanied by an increased formation of malondialdehyde.3. When CoA is added to the microsomes together with a source of oxaloacetate and the condensing enzyme synthase, the etherase present forms citrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Studies were performed on metabolism which yielded acetaldehyde and ethanol as products [22]. The ether was found to undergo an oxygen uptake in rat liver microsomal membrane [23]. These observations are in line with the oxidative metabolism outlined in Scheme 2 which entails initial conversion to a carbon radical followed by oxidation to hydroperoxide with decomposition to the metabolites.…”
Section: Etherssupporting
confidence: 61%
“…Studies were performed on metabolism which yielded acetaldehyde and ethanol as products [22]. The ether was found to undergo an oxygen uptake in rat liver microsomal membrane [23]. These observations are in line with the oxidative metabolism outlined in Scheme 2 which entails initial conversion to a carbon radical followed by oxidation to hydroperoxide with decomposition to the metabolites.…”
Section: Etherssupporting
confidence: 61%
“…We have stated previously (Peters & Shorthouse, 1975) (1) that there is no increase in the O-oxidase after treating rats with phenobarbitone, which is known to induce increases in several enzymes, and (2) that the enzyme is present in microsomes collected between 12,000 and 100,000 g, no addition of a folate was necessary and a 'folate' inhibitor had no effect. Point (1) was further confirmed by experiments in which Dr P. Rich kindly collaborated.…”
Section: Resultsmentioning
confidence: 99%
“…Homogenates of the various livers were made as described previously for rat liver (Peters & Shorthouse, 1975), as also were the measurement of 02 uptake. (It was found that in the presence of long-chain fatty acids the membrane of the electrode soon became insensitive, presumably due to blocking by the fatty acid.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation